Multiple‐pathways of carbon dioxide binding by a Lewis acid [B(C6F5)3] and a lewis base [P(tBu)3]: The energy landscape perspective. Issue 4 (7th October 2013) - Pu, Maoping; Privalov, Timofei
<x xml:space="preserve">Abstract</x> Using the reaction‐relevant two‐dimensional potential energy surface, an accurate reaction‐pathway mapping and ab inito molecular dynamics, it is shown that CO2 capture by P(tBu)3 and B(C6F5)3 species has many nearly degenerate reaction‐routes to take. The explanation of that is in the topography of the transition state (saddle) area. An ensemble of asynchronous reaction‐routes of CO2 binding is described in fine detail. © 2013 Wiley Periodicals, Inc.